PRAGMATIC ASPECTS OF OCCASIONAL MODIFICATIONS IN ENGLISH PHRASEOLOGY - Fayzullayeva Malika Jamshid qizi (Modern American Journals, 2025)
This paper investigates the pragmatic aspects of occasional modifications in English phraseology, focusing on how speakers creatively adapt conventional phraseological units to meet communicative and contextual needs. The study explores the role of intention, context, and discourse function in shaping occasional variants of idioms, proverbs, and fixed expressions. By analyzing examples from modern media, literature, and everyday speech, the research demonstrates that pragmatic modification serves expressive, evaluative, humorous, and persuasive purposes, enriching the dynamic nature of phraseological usage in English discourse.
Keywords: Phraseology, pragmatics, occasional modification, idiom variation, communicative intention, discourse function, creativity.